Penerapan Terapi Kelompok Terapeutik sebagai Upaya Optimalisasi Perkembangan Industri Anak Usia Sekolah - Fitria, Yeni; Dewi, Erti Ikhtiarini; Kurniyawan, Enggal Hadi; Deviantony, Fitrio (Universitas Nusantara PGRI Kediri, 2024)
This community service aims to increase knowledge about school age development and provide development stimulation to optimize the development of school-age children's industry/work. Solutions that can be provided to partners are 1) conducting an initial assessment as basic data to determine the achievement of school-age children's industry development tasks, 2) increasing children's knowledge about school-age development, and 3) conducting therapeutic group therapy by providing stimulation for school-age children's development (motor, cognitive, language, emotions and personality, moral and spiritual, and psychosocial development). The implementation of activities consists of three stages, namely the preparation, implementation, and evaluation stages. The achievement of the objectives of this community service is seen from the results of the evaluation of school-age children's development. The results of this activity show that after participating in Therapeutic Group Therapy (TKT), most students experienced an optimal and positive increase in their abilities in their development levels. Therefore, we recommend the use of therapeutic group therapy as an effort to stimulate children's development to the maximum, which will ultimately have a positive impact on the development of school-age children's industry or work.